PARTICIPATION OF BEGINNER VOTER IN THE 2024 ELECTION IN KUNINGAN DISTRICT - Maulana Sobirin, Ade; Fauziah, Resna; Zulkarnaen, Iskandar; Haryo Bharoto, R. Mahendra (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2024)
The participation of novice voters in the 2024 elections in Kuningan Regency is already underway but is considered still not optimal due to a lack of basic understanding regarding the importance of participation in elections, apathy towards the political system and their low trust in the government. This research aims to find out how novice voters participate in the 2024 elections in Kuningan Regency. The research method used was descriptive qualitative with data collection techniques in the form of observation, interviews, and documentation. Using the theory of the influence of community participation according to Bintoro Tjokroamidjojo as a theoretical framework. The results of this research indicate that voter participation in the 2024 elections in Kuningan Regency is considered not yet optimal if viewed from the results of the vote acquisition during the election because the number of invalid votes is still quite large. These results cannot be separated from the participation of first-time voters in it. Things that influence the participation of first-time voters are the lack of voter trust in the government and political institutions, the delivery of election-related information to first-time voters is still not conveyed thoroughly, and the political knowledge and understanding of new voters is still minimal. So even though the election was welcomed enthusiastically by first-time voters, there were still many invalid votes which was an indicator that in their participation they had not been able to use their voting rights properly.